2015
DOI: 10.18632/oncotarget.5628
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic induction of apoptosis by salinomycin and gefitinib through lysosomal and mitochondrial dependent pathway overcomes gefitinib resistance in colorectal cancer

Abstract: Here, we showed the antibiotic salinomycin (SAL) combined with GEF exerted synergistic cytotoxicity effects in colorectal cancer cells irrespective of their EGFR and KRAS status, with a relatively low toxicity to normal cells. Additionally, combination of the two drugs overcame Ras-induced resistance and the acquired resistance to GEF. Further, we identified a new potential mechanism of this cooperative interaction by showing that GEF and SAL acted together to enhance production of reactive oxygen species (ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…For luciferase assay, the 293T and A549 cells were cultured in 24-well plates and transfected with 500 ng of either pGL3-FOXM1 or pGL3-control vector and 50 pmol of miR-509- [25].…”
Section: Dual-luciferase Activity Assaymentioning
confidence: 99%
“…For luciferase assay, the 293T and A549 cells were cultured in 24-well plates and transfected with 500 ng of either pGL3-FOXM1 or pGL3-control vector and 50 pmol of miR-509- [25].…”
Section: Dual-luciferase Activity Assaymentioning
confidence: 99%
“…Salinomycin was also utilized as additive in several other combinational treatment approaches overcoming acquired drug resistance [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is an important treatment strategy for solid tumors, and one of the main treatment methods for CRC (17,18). Apoptosis is one of the main signs of effective anticancer chemotherapy; however, due to drug resistance, the apoptotic effects of drugs on the tumor cells are weakened and a large proportion of patients respond poorly to chemotherapy (19,20). At present, drug resistance of tumor cells is one of the main reasons for chemotherapy failure (21).…”
Section: Mirnas and Chemotherapy For Crcmentioning
confidence: 99%
“…By contrast, inhibition of miRNA-587 may enhance the expression of PPP2R1B in CRC cells, which increases sensitivity to 5-FU treatment. Previous studies indicated that miRNA-302a expression is decreased in CRC cells, and high expression of miRNA-302a inhibits cell proliferation through inactivating ERK1/2 and PI3K/AKT (17,20). Oxaliplatin (L-OHP) is a third-generation platinum-based chemotherapy agent.…”
Section: Mirnas and Chemotherapy For Crcmentioning
confidence: 99%